Evaluation of improved stoves CETA hybrid type, part of the program TERRENA earthly program in vulnerable communities in the department of Jinotega (Revista Científica Estelí, 2015)
The main objective of this research is to evaluate the improved stoves CETA Hybrid type, implemented in communities of Jinotega, its impacts on the lives of its users and the environment. It is a quantitative research, it is exploratory, descriptive and correlational. The study sample is probabilistic, 36 improved stoves and 36 families. The instruments used were: survey based on a structured questionnaire, controlled cooking test to measure the performance of the upgraded kitchen, equipment for measuring particles and carbon monoxide were installed. The results show that the improved stoves pollute less the interior of the houses than the traditional ones, due to the efficiency and design with chimney. The improved stoves consume less wood, less cooking time, decrease the respiratory diseases. The improved stoves without chimney pollute more than traditional ones. It is concluded that the use of these stoves is more efficient than traditional ones due to its design and greater concentration of heat in the combustion chamber, the less clear-cutting of forests and also due to the lack of follow up the project, most of these stoves are damaged.Keywords: Improved cook, carbon monoxide, particulate matter.